The Effect of Pin Length and Compression Force in Double Side Friction Stir Welding on Tensile Strength of AA1100 - Andiansyah, Mochamad; Setiawan, Agus (Evrimata: Journal of Mechanical Engineering, 2024)
Friction Stir Welding (FSW) is solid state welding without additives and does not produce pollution. There are two FSW welding methods, namely single side (FSW) and double side (DFSW). The FSW process in previous studies using aluminum materials, especially AA 1100 type, has not obtained optimum joint strength. Therefore, it is necessary to conduct a research study on improving the quality of tensile strength of welding results using the DFSW method on AA1100. The purpose of this study is to determine the effect of variations in pin length and compressive force on the maximum tensile strength of the results of Double Side Friction Stir Welding Aluminum Alloy 1100 welding joints. The method used in this research is experimental. The welding process uses Double Side Friction Stir Welding, by varying two independent variables namely pin length 1.5 mm, 2 mm, 2.5 mm and compressive force 30 kg, 35 kg, 40 kg, 45 kg. The controlled variables used include travel speed (10 mm/min), heating temperature (250℃), shoulder diameter (25 mm), heating plate width (10 mm), and Aluminum AA1100 plate thickness (3.5 mm), with butt joint type welding. The data analysis used is Factorial Design of Experiment (DOE). The results of this study indicate that pin length and compressive force affect the tensile strength of AA1100 material welds. The maximum tensile strength value of DFSW welding results is 90.16 MPa or 80.5% of the tensile strength of the parent material. The maximum tensile strength value was obtained from the interaction of 2 mm pin length and 45 kg compressive force.